2003
DOI: 10.1086/375143
|View full text |Cite
|
Sign up to set email alerts
|

A Whole-Genome Scan in 164 Dutch Sib Pairs with Attention-Deficit/Hyperactivity Disorder: Suggestive Evidence for Linkage on Chromosomes 7p and 15q

Abstract: A genome scan was performed on 164 Dutch affected sib pairs (ASPs) with attention-deficit/hyperactivity disorder (ADHD). All subjects were white and of Dutch descent and were phenotyped according to criteria set out in the Diagnostic and Statistical Manual Of Mental Disorders, 4th edition. Initially, a narrow phenotype was defined, in which all the sib pairs met the full ADHD criteria (117 ASPs). In a broad phenotype, additional sib pairs were included, in which one child had an autistic-spectrum disorder but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
172
2
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(185 citation statements)
references
References 56 publications
(61 reference statements)
7
172
2
4
Order By: Relevance
“…3 In this scan our initial nonparametric LOD score value of 2.89 next to the marker D5S2005 (1.40 Mb) was obtained within a broad peak extending from the distal end of 5p to beyond 60 cM; our subsequent fine-mapping efforts resulted in a nonparametric LOD score of 2.78 at 17 cM. 3 Ogdie et al 6 localized their 5p peak in 308 ASPs to 59 cM (MLS (maximum LOD score) 2.55), whereas Bakker et al 64 reported an MLS of 1.43 at 69 cM in 164 ASPs. In light of the small sample sizes, which lead to considerable stochastic variation of the location of linkage peaks, 65 it seems plausible to assume that genetic variation at the same locus (or loci) underlies these chromosome 5p linkage peaks.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…3 In this scan our initial nonparametric LOD score value of 2.89 next to the marker D5S2005 (1.40 Mb) was obtained within a broad peak extending from the distal end of 5p to beyond 60 cM; our subsequent fine-mapping efforts resulted in a nonparametric LOD score of 2.78 at 17 cM. 3 Ogdie et al 6 localized their 5p peak in 308 ASPs to 59 cM (MLS (maximum LOD score) 2.55), whereas Bakker et al 64 reported an MLS of 1.43 at 69 cM in 164 ASPs. In light of the small sample sizes, which lead to considerable stochastic variation of the location of linkage peaks, 65 it seems plausible to assume that genetic variation at the same locus (or loci) underlies these chromosome 5p linkage peaks.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, we cannot exclude that other genes may also contribute to our original linkage at 17 cM 3 and to the peaks on 5p found by other groups. 6,64 In general, all of the aforementioned findings were stronger in the GS subset. The 54 new families, which included affected sib pairs thus allowing linkage analysis, did not show such a strong linkage as the original 102 GS families.…”
Section: Discussionmentioning
confidence: 85%
“…Some genes involved may have pleiotropic effects. Thus, it has been suggested that AD/HD and reading disability [6,147,185], and AD/HD and autism [6,147] share genetic susceptibility factors.…”
Section: Influences On Pathogenesismentioning
confidence: 99%
“…Owing to their inherent features, tandem repeats have been widely used in genetic fingerprinting and as the genetic markers in linkage studies to locate the chromosomal regions harboring the mutations or genes for monogenic or familial disorders, complex diseases and quantitative traits. [41][42][43][44] Although tandem repeats are more informative than SNPs at the individual marker level, their number is far less than the several million SNPs in the human genome. Thus, tandem repeats are not ideal genetic markers for applications that require high marker density or resolution, such as genome-wide association studies (GWASs), in which several hundred thousand of SNPs are needed.…”
Section: The Evolution Of Genetic Markers In Disease Gene Mappingmentioning
confidence: 99%
“…However, microsatellites were widely used as the genetic markers in linkage studies. [41][42][43][44] These genetic variations have been used as the markers in human genetic studies for more than 20 years until the completion of the Human Genome Project 50 and the finding of millions of SNPs by the International SNP Map Working Group and other studies. 5,6 Thereafter, SNPs became the primary markers in genetic association studies, and also replaced microsatellites in some linkage studies.…”
Section: The Evolution Of Genetic Markers In Disease Gene Mappingmentioning
confidence: 99%